MODEL STRINGER “ LOOK THINK ACT “TERHADAP KEMANDIRIAN PEREMPUAN KORBAN TRAFFICKING DI BOGOR - Nurhayati, Titi; Rosaria, Yohana Wulan; Fitria, Dedes (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Jandri Community is a group formed around 2004 consisting of women without husbands (divorced or independent widows because they are not married but have family responsibilities, biological children or foster children), aiming to establish friendship among members to exchange ideas for mutual support, other goals are physically and economically independent. This group consists of 30 people from backgrounds who have experienced sexual exploitation (prostituted, trafficked by others and those closest to them). This study aims to determine the application of the Stringer Look Think Act Model to the independence of women victims of Trafficking in Bogor. The study design uses the Action research design with sequential explanatory mixed methods. Data collection and analysis of quantitative data in the first stage, then followed by qualitative data collection in the second stage to strengthen the results of quantitative research. The results showed that the application of the look model could be used to determine the characteristics of respondents. The application of the thought model can be used to analyze the needs of respondents. The application of the act model can be used to implement a model that is deemed appropriate to the needs of the respondents. It is recommended that institutions dealing with the handling of women victims of trafficking use the Stringer Look Think Act model approach to approach women trafficking victims  to explore problems and prevent the transmission of sexually transmitted infections and HIV / AIDS using voluntary counselling and testing